2011
DOI: 10.1089/thy.2011.0059
|View full text |Cite
|
Sign up to set email alerts
|

Higher Intratumoral Expression of CD1a, Tryptase, and CD68 in a Follicular Variant of Papillary Thyroid Carcinoma Compared to Adenomas: Correlation with Clinical and Pathological Parameters

Abstract: We highlight a higher presence of immunological cells in carcinomas than in adenomas. On this basis, it is possible to speculate that these inflammatory elements could be involved in tumor progression and invasion, as appears to be the case for MC and M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 30 publications
3
39
1
Order By: Relevance
“…Mast cell density was found to correlate with extrathyroidal extension and invasiveness, opening avenues for therapeutic intervention of these mast cell mediators [34]. Lastly, mast cells were significantly more abundant in the intratumoral and peritumoral regions of follicular variant of PTC compared to adenoma, suggesting its usefulness in distinguishing between benign and malignant forms of follicular thyroid lesions [42].…”
Section: Tumor Metabolism and The Microenvironment In Thyroid Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…Mast cell density was found to correlate with extrathyroidal extension and invasiveness, opening avenues for therapeutic intervention of these mast cell mediators [34]. Lastly, mast cells were significantly more abundant in the intratumoral and peritumoral regions of follicular variant of PTC compared to adenoma, suggesting its usefulness in distinguishing between benign and malignant forms of follicular thyroid lesions [42].…”
Section: Tumor Metabolism and The Microenvironment In Thyroid Cancermentioning
confidence: 96%
“…For instance, high T-regulatory cell density correlates with thyroid cancer aggressiveness, and an increased number of immunoregulatory natural killer cells has been demonstrated in PTC compared to normal tissues [39,40]. Furthermore, is has been shown that the degree of lymphocyte and immature dendritic cell infiltration correlated with better prognosis in PTC [41,42], whereas increased macrophage density in poorly differentiated thyroid carcinoma correlated with invasive features and worsened prognosis [43]. Jung et al found that tumor-associated macrophage density correlated with more aggressive subtypes, like anaplastic thyroid carcinoma [44].…”
Section: Tumor Metabolism and The Microenvironment In Thyroid Cancermentioning
confidence: 99%
“…24 A higher MC density was also found in FTC compared with adenomas and correlated with extracapsular extension. 79 TC cell line CM induced in vitro MC chemotaxis through the release of VEGF-A, 24 which activated the VEGFRs on human MCs. 53,80 In addition, TC cells activated MCs to release cytokines (IL-6, TNF-a, GM-CSF) and chemokines (CXCL10/ IP10 and CXCL1/Gro-a).…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 97%
“…Already the first studies showed significant differences in the intensity of S-100 + DCs infiltration in particular types of thyroid carcinoma with PTC specimens characterized by the highest DCs density [84,85]. Such observation was confirmed in further analyses, demonstrating significantly higher accumulation of S-100 + DCs or CD1a + immature DCs in PTC as compared with follicular carcinomas [68,86,87], medullary carcinomas [69] and poorly differentiated and undifferentiated carcinomas [87,88], as well as adenomas [86,[89][90][91] and benign thyroid nodules [92]. The abundant DCs infiltration in PTC was observed in all tumour histotypes including diffuse sclerosing variant [86,88,93,94].…”
Section: Thyroid Cancermentioning
confidence: 86%
“…However, DCs expressing another maturation marker -Lysosomal-Associated Membrane Protein (LAMP) were found also in the intratumoural area [86,91]. Most importantly, the study comparing DC infiltration in follicular variant of PTC and thyroid adenomas, revealed significantly increased numbers of CD1a + immature DCs in PTC, whereas mature LAMP + DCs accumulated to similar extent in malignant and benign thyroid tumours [91].…”
Section: Thyroid Cancermentioning
confidence: 99%